Analysis of Factors Associated with Neonatal Mortality - Syarifah; Mayetti; Defrin (LPPM Universitas Harapan Bangsa, 2024)
Neonatal mortality remains a leading cause of infant death despite being a key factor in child health and survival. This study analyzed factors related to neonatal mortality at Rokan Hulu District General Hospital using a quantitative, retrospective case-control approach. The 68 respondents (34 cases, 34 controls) were selected through purposive sampling. Data analysis used a logistic regression model. Prematurity emerged as the most influential variable (p=0.019), carrying a 4.344 times higher risk of neonatal death versus full-term births, after controlling for low birth weight and respiratory distress syndrome.